Penegakan Hukum Terhadap Anak Korban Bullying Di Sekolah Menengah Pertama : Studi Kasus Di Wilayah Stabat - Juantilo Gurusinga; Muhammad Hasan Sebyar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Bullying is a serious problem that occurs in the school environment and can have a negative impact on children. Bullying includes intimidation, physical violence, verbal abuse, and emotional thinking towards vulnerable victims by a person or group of people. The aim of this research is to examine legal protection for children who are victims of bullying in the junior high school environment. Bullying has become a big problem in educational environments, where children often experience physical, verbal and emotional violence. This study focuses on analyzing the legal framework that exists to protect these young victims and ensure their well-being in the school environment. This research is empirical legal research, using a statutory-regulatory approach (legislative approach) and a legal sociological approach (socio-legal approach). The results of this research indicate the need for comprehensive legal action to eradicate bullying in junior high schools, including prevention strategies, effective reporting mechanisms, and appropriate disciplinary action against perpetrators. In addition, this study emphasizes the need for the role of schools and the state in creating a safe and supportive environment for children, where incidents of bullying are promptly addressed and the rights of victims are protected.